PERUBAHAN KADAR SENYAWA BIOAKTIF DAN AKTIVITAS ANTIOKSIDAN BERAS ORGANIK HITAM VARIETAS Jawa DENGAN PENGEMAS POLIPROPILEN SELAMA ENAM BULAN PENYIMPANAN - Kohartono, Gabriella; Sutedja, Anita Maya; Widyawati, Paini Sri (Widya Mandala Surabaya Catholic University, 2014)
The importance of health awareness has increased so the consumption of organic products has increased. Java varieties black organic rice is one of the local organic rice grown in Indonesia. Pigmented rice contains bioactive compounds that can act as antioxidants. Rice needs to be packaged to minimize damage and facilitate the storage using polypropylene (PP) packaging. The results showed an increase in the yield, bioactive compounds, and antioxidant activities during storage. The highest yield of black rice (12.08 ± 0.03% dry basis) was at the 4th month. Total phenol of black rice (10.55 ± 0.29 mg Gallic Acid Equivalent/g dry basis) and total anthocyanins (0.04 ± 0.00 mg Cyanidin-3-Glucoside Equivalent/g dry basis) was the highest at 3rd month, total flavonoids (2.10 ± 0.11 mg Catechin Equivalent/g dry basis) at 6th month, the free radical DPPH scavenging (1.53 ± 0.03 mg GAE/g dry basis) activity at 3rd month, and the iron reducing power (31.31 ± 2.05 mg GAE/g dry basis) at 4th month.